Preparation method of resin-based composite material used in high-temperature environment and preparation method of resin-based composite material
By adding and modifying micron-scale diamonds into resin-based friction materials, the problems of unstable friction coefficient and wear weight in high-temperature environments are solved, and appropriate high-temperature friction performance and low wear rate are achieved, which extends the service life.
Patent Information
- Application Number
- CN202411854266.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure CN119684790A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resin-based friction materials, and in particular to the preparation and method of a resin-based composite material for large automobiles in a high-temperature environment. Background Art
[0002] Resin-based friction materials are widely used in aerospace, rail transit, industrial and agricultural machinery and other fields due to their advantages such as easy formula design, light weight, high strength and simple process. They are usually composed of four parts: binder, reinforcing phase, friction reducer and filler. Due to the large amount of friction heat generated by the dual material during emergency braking, the contact interface temperature rises, resulting in thermal decay, which in turn causes the friction coefficient of the material to decrease and the wear to increase, which ultimately seriously affects the service safety and service life. Therefore, it is urgent to prepare a resin-based friction material with a suitable and stable friction coefficient and a low volume wear rate in a high temperature environment.
[0003] In order to effectively improve the mechanical and friction and wear properties of resin-based friction materials, the main methods currently used are to correctly select the type, content and size of raw materials and to enhance the interface bonding strength between inorganic fillers and resins. Studies have shown that the average friction coefficient of friction materials prepared with phenolic resin as a binder at 150°C is less than 0.20, and the volume wear rate reaches 2×10 -13 m 3 / Nm. The volume wear rate of the friction material prepared by using polyimide resin as the binder at 200°C can reach 6×10 -15 m 3 / Nm, but its average friction coefficient is only 0.30. In addition, although the friction material prepared by adding 1.6% (mass fraction) nanodiamond has a higher hardness, its average friction coefficient is only 0.10, and the volume wear rate reaches 10 -12 m 3 / Nm level. At the same time, the Chinese patent "A modified diamond micropowder epoxy resin composite material and its preparation method" with publication number CN118126498A provides a modified diamond micropowder epoxy resin composite material and its preparation method. The diamond modified by the coupling agent has a stronger bond with the epoxy resin, but its average friction coefficient is only 0.019, which cannot be used in the field of high-temperature braking. Therefore, it is urgent to develop a resin-based composite material with good mechanical strength, a suitable and stable high-temperature friction coefficient (0.35-0.60) and a low volume wear rate. Summary of the invention
[0004] The purpose of the present invention is to improve the mechanical and high-temperature friction and wear properties of a resin-based composite material by adding micron-sized diamonds, and to provide a preparation method of a resin-based composite material used in a high-temperature environment.
[0005] In order to achieve the above object, the present invention provides the following scheme:
[0006] The present invention provides a preparation method of a resin-based composite material used in a high temperature environment, and the preparation method comprises the following steps:
[0007] (1) Surface modification of fibers and diamonds to enhance the interfacial bonding between them and the resin;
[0008] (2) Weigh powders in order according to the mass fractions of 0% to 30% binder, 0% to 40% reinforcing fiber, 0% to 20% friction reducer, 0% to 30% diamond, and 0% to 60% filler;
[0009] (3) The raw materials are then placed in a ball mill for dry mixing, and dried after the dry mixing is completed;
[0010] (4) placing the dried powder into a pretreated mold for hot pressing and sintering, keeping the temperature, and then cooling to room temperature in the furnace to obtain the resin-based composite material.
[0011] Furthermore, the surface modification solution in step (1) is a mixed solution of a silane coupling agent, water and ethanol in a mass ratio of 1:1:8, and is subjected to 10 minutes of ultrasonic dispersion and 2 hours of pre-hydrolysis to achieve uniform mixing.
[0012] Furthermore, in step (1), the mass ratio of diamond to hydrolyzate is 1:4, and the heating temperature and stirring time are 80° C. and 4 h, respectively.
[0013] Furthermore, the binder in step (2) is one of thermosetting resins with a curing temperature higher than 200° C., such as polyimide resin, epoxy resin, phenolic resin, silicone resin, polybenzimidazole, etc., and the particle size of the binder is in the range of 10 to 50 μm. The function of the binder is to bond the components into a whole.
[0014] Furthermore, the reinforcing fiber in step (2) is one of chopped carbon fiber, glass fiber, and SiC fiber, and the reinforcing fiber is in a single crystal state, with a length range of 0.1 to 10 μm and a diameter range of 50 to 600 nm. The function of the reinforcing fiber is to bear external loads.
[0015] Furthermore, the friction reducer in step (2) is one or two of flake graphite, graphite, MoS2, and WS2 lubricating phases, and the particle size of the friction reducing particles ranges from 150 to 250 μm. The function of the flake graphite is to improve friction stability and reduce noise.
[0016] Furthermore, the diamond in step (2) is a pyramid-shaped, micron-sized particle with a particle size range of 50 to 150 μm. The role of the diamond is to improve the mechanical strength, high-temperature friction coefficient and reduce the volume wear rate. Figure 1 and Figure 2 They are respectively the microscopic morphology and particle size distribution diagram of the diamond used in Examples 1 to 4 of this article.
[0017] Furthermore, the filler in step (2) is one or two of inorganic substances such as barium sulfate, calcium carbonate, magnesium sulfate, etc., and the filler particle size ranges from 5 to 15 μm. The function of the filler is to fill the volume.
[0018] Furthermore, step (3) is dry-mixed in a vertical planetary ball mill.
[0019] Furthermore, in step (3), the raw materials except the reinforcing fiber are dry-mixed in a vertical planetary ball mill at a speed of 150 r / min for 10 hours, and then the reinforcing fiber is added and dry-mixed at a speed of 150 r / min for 2 hours.
[0020] Furthermore, the drying in step (3) is carried out in an electric heated air drying oven.
[0021] Furthermore, step (3) is dried at 60° C. for 12 h.
[0022] Furthermore, the pre-treated mold in step (4) is a mold that has been cleaned with alcohol and has a layer of 0.01 mm thick graphite release paper padded on the upper and lower surfaces.
[0023] Furthermore, during the hot pressing sintering in step (4), the temperature is first raised from room temperature to 150°C at a heating rate of 10°C / min at 10 MPa, then kept at 150°C at 30 MPa for 0.5 h, and then raised from 150°C to 260°C at a heating rate of 8°C / min at 10 MPa, and then kept at 260°C at 30 MPa for 1 h, and finally cooled to room temperature with the furnace.
[0024] The invention provides a preparation method of a resin-based composite material used in a high temperature environment.
[0025] The present invention also provides the use of the resin-based composite material in friction materials for large trucks. The average friction coefficient of the composite material should be controlled within the range of 0.35 to 0.60.
[0026] The present invention discloses the following technical effects:
[0027] The present invention improves the mechanical and high-temperature friction and wear properties of resin-based composite materials by adding micron-sized diamonds. Compared with related studies, the resin-based composite material obtained by adding 4% (mass fraction) diamonds has a significantly different organizational morphology, close bonding between components, high hardness and compression strength, and a suitable and stable high-temperature friction coefficient and a low volume wear rate, and has good application value in the field of friction materials for large trucks. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0029] Figure 1 The microscopic morphology of diamond used in Examples 1 to 4 of the present invention;
[0030] Figure 2 The particle size distribution diagram of diamond used in Examples 1 to 4 of the present invention;
[0031] Figure 3 The infrared spectra of diamond used in Examples 1 to 4 of the present invention before and after modification;
[0032] Figure 4 It is the sintering process curve diagram of Examples 1 to 4 of the present invention;
[0033] Figure 5 This is a microscopic morphology of the resin-based composite material prepared in Example 1 of the present invention before wear;
[0034] Figure 6 This is a microscopic morphology of the resin-based composite material prepared in Example 1 of the present invention after wear;
[0035] Figure 7 The friction coefficient curves of the resin-based composite materials prepared in Examples 1 and 3 of the present invention;
[0036] Figure 8 Graphs showing the high temperature friction coefficient and volume wear rate of the resin-based composite materials prepared in Examples 1 and 3 of the present invention. DETAILED DESCRIPTION
[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0038] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the stated range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art to which the invention belongs. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation and testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention without departing from the scope or spirit of the present invention.The present invention description and examples are intended to be exemplary only.
[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended words, meaning including but not limited to.
[0042] Example 1
[0043] (1) Weigh 1.80 g of polyimide resin powder, 1.50 g of chopped carbon fiber, 0.80 g of flake graphite, 0.40 g of diamond powder, and 5.50 g of barium sulfate (mass fractions are 18%, 15%, 8%, 4%, and 55%, respectively), pour the raw materials except the fiber into a mixing tank, and then put them into an XQM-2 vertical planetary ball mill and dry mix them at a speed of 150 r / min for 10 h, then pour the chopped carbon fiber into it and dry mix it at a speed of 150 r / min for 2 h, and then pour the powder into a beaker and place it in a 101-2A electric heating blast drying oven, and dry it at 60°C for 12 h.
[0044] (2) Clean the mold with alcohol and place a layer of graphite release paper (0.1 mm thick) on the upper and lower surfaces of the mold. Slowly pour the powder in step (1) into the mold and flatten it. Then, hot press sinter it in a HTEYP-30 flat plate vulcanizer to obtain a 20×20×5 mm 3The sample was first heated from room temperature to 150°C at a heating rate of 10° / min under 10MPa during sintering, then kept warm at 30MPa and 150°C for 0.5h, then heated from 150°C to 260°C at a heating rate of 8° / min under 10MPa, then kept warm at 30MPa and 260°C for 1h, and finally cooled to room temperature with the furnace. The material prepared in this embodiment is recorded as sample J1.
[0045] The infrared spectra of the diamond used in Examples 1 to 4 before and after modification are shown in Figure 3 ; The sintering process curves of Examples 1 to 4 are shown in Figure 4 The microscopic morphology of the resin-based composite material prepared in Example 1 before wear is shown in Figure 5 The microstructure of the resin-based composite material prepared in this embodiment after wear is shown in Figure 6 .
[0046] Take sample J1 and use HRA-150 Rockwell hardness tester to test the hardness of the composite material. The hardness test points of each sample are 5 points evenly distributed on the surface of the sample, and the average value is taken as the hardness of the sample. The compression test is carried out on WDW-100C electronic universal testing machine. The sample size is 10×10×5mm 3 The loading rate is 0.01 mm / s. The compressive strength of the material is obtained by collecting the stress-strain values during the compression process. Each sample is measured three times, and the average value is taken as the final compressive strength of the sample.
[0047] Take sample J1 and test its friction and wear performance on a CFT-I friction and wear testing machine. The sample size is 20×20×5mm. 3 , the counterpart is a high chromium steel ball with a diameter of 6mm and a Rockwell hardness of 60HRC. Before the test, the sample and the counterpart were polished with sandpaper and cleaned with alcohol to improve the reliability of the data obtained during the test. The test was carried out under dry friction conditions, with a test load of 20N, a test temperature of 200℃, a reciprocating number of 500t / min, a reciprocating length of 5mm, and a reciprocating time of 60min.
[0048] Example 2
[0049] 1.80 g of polyimide resin, 1.50 g of chopped carbon fiber, 0.80 g of flake graphite, 0.80 g of diamond, and 5.10 g of barium sulfate (mass fractions of 18%, 15%, 8%, 8%, and 51%, respectively) were weighed respectively. The mixing, drying, preparation process, and characterization methods were the same as those in Example 1. The material prepared in this example is recorded as sample No. J2.
[0050] Example 3
[0051] 1.80 g of polyimide resin, 1.50 g of chopped carbon fiber, 0.80 g of flake graphite, 1.20 g of diamond, and 4.70 g of barium sulfate (mass fractions of 18%, 15%, 8%, 12%, and 47%, respectively) were weighed respectively. The mixing, drying, preparation process, and characterization methods were the same as those in Example 1. The material prepared in this example is recorded as sample No. J3.
[0052] Example 4
[0053] 1.80 g of polyimide resin, 1.50 g of chopped carbon fiber, 0.80 g of flake graphite, 1.60 g of diamond, and 4.30 g of barium sulfate (mass fractions of 18%, 15%, 8%, 16%, and 43%, respectively) were weighed respectively. The mixing, drying, preparation process, and characterization methods were the same as those in Example 1. The material prepared in this example is recorded as sample No. J4.
[0054] Performance Characterization Results
[0055] The friction curves of the resin-based composite materials prepared in Example 1 and Example 3 are shown in Figure 7 The high temperature friction coefficient and volume wear rate of the resin-based composite materials prepared in Example 1 and Example 3 are shown in Figure 8 . Table 1 shows the test results of the physical and mechanical properties of the resin-based composite materials JI-J4 samples obtained in Examples 1-4, and Table 2 shows the test results of the friction and wear properties of the resin-based composite materials JI-J4 samples obtained in Examples 1-4. It can be seen from the test results that the resin-based composite material prepared by adding micron-sized diamonds in the present invention has high hardness and compression strength, and can withstand the forces during processing and use. At the same time, it was found that adding 4% (mass fraction) diamond can effectively improve the high-temperature friction coefficient of the composite material and reduce the volume wear rate, so that the service safety is guaranteed and the service life is effectively extended.
[0056] Table 1 Physical and mechanical properties of composite materials
[0057]
[0058] Table 1 Physical and mechanical properties of composite materials
[0059]
[0060] It can be seen from the above embodiments that the present invention greatly improves the mechanical and high-temperature friction and wear properties of the resin-based composite material by adding micron-sized diamonds, ensures safety during service and prolongs the service life, and has good application value.
[0061] The resin-based composite material prepared by adding micron-sized diamonds in the present invention has a unique organizational morphology, with components tightly bonded together, and at the same time has high hardness and compression strength, a suitable and stable high-temperature friction coefficient and a low volume wear rate, and has good application value in the field of friction materials for large trucks.
[0062] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A preparation method of a resin-based composite material used in a high temperature environment and a method thereof, characterized in that: The preparation comprises the following steps: (1) Surface modification of fiber and diamond is performed to enhance the interfacial bonding between the fiber and the resin; (2) 0% to 30% binder, 0% to 40% reinforcing fiber, 0% to 20% friction reducer, 0% to 30% diamond, and 0% to 60% filler are weighed in a mixing tank in order; (3) the powders are then mechanically mixed, and after the mixed powders are evenly mixed, the mixed powders are dried; (4) the mixed powders are placed in a pretreated mold for hot pressing and sintering, and after the heat preservation is completed, the mixed powders are cooled to room temperature in the furnace to obtain the resin-based composite material.
2. The preparation method of a resin-based composite material used in a high temperature environment according to claim 1, characterized in that: The binder in step (2) is one of thermosetting resins with a curing temperature higher than 200° C., such as polyimide resin, epoxy resin, phenolic resin, silicone resin, polybenzimidazole, etc., and the particle size range of the binder is 10 to 50 μm.
3. The preparation method of a resin-based composite material used in a high temperature environment according to claim 1, characterized in that: The reinforcing fiber in step (2) is one of chopped carbon fiber, glass fiber, and SiC fiber. The reinforcing fiber is in a single crystal state, with a length ranging from 0.1 to 10 μm and a diameter ranging from 50 to 600 nm.
4. The preparation method of a resin-based composite material used in a high temperature environment according to claim 1, characterized in that: The friction reducer in step (2) is one or two of the lubricating phases selected from the group consisting of flake graphite, graphite, MoS2, and WS2, and the particle size of the friction reducing particles is in the range of 150 to 250 μm.
5. The preparation method of a resin-based composite material used in a high temperature environment according to claim 1, characterized in that: The diamonds in step (2) are pyramidal, micron-sized particles with a particle size ranging from 50 to 150 μm.
6. The preparation method of a resin-based composite material used in a high temperature environment according to claim 1, characterized in that: The filler in step (2) is one or two of inorganic substances such as barium sulfate, calcium carbonate, magnesium sulfate, etc., and the particle size range of the filler is 5 to 15 μm.
7. The preparation method of a resin-based composite material used in a high temperature environment according to claim 1, characterized in that: In step (4), the temperature is first increased from room temperature to 150°C at a heating rate of 10°C / min at 10 MPa, then kept at 150°C at 30 MPa for 0.5 h, and then increased from 150°C to 260°C at a heating rate of 8°C / min at 10 MPa, then kept at 260°C at 30 MPa for 1 h, and finally cooled to room temperature with the furnace.
8. The resin-based composite material prepared according to claims 1 to 7 is used in the field of friction materials for large trucks.
Citation Information
Patent Citations
Modified diamond micro-powder epoxy resin composite material and preparation method thereof
CN118126498A
Method for synergistically modifying resin-based composite material through silicon carbide-tungsten disulfide
CN113480848A
Binder for producing frictional carbon-carbon composite materials, method of producing material and material
RU2484035C1